Kesalahan Pemahaman pada Konsep dalam Belajar Fisika bagi Siswa SMAN di Jawa Timur Ditinjau Dari Beberapa Faktor Internal dan Eksternal yang Mempengaruhinya - Kadim Masjkur; Sutarman Sutarman; Asim Asim; Agus Suyudi (Universitas Negeri Malang, 2016)
The misconception that the SMAN students have concerning physics is very serious which effects the formal reasoning ability of the students and the teaching ability of the teachers. Though lab work has no direct influence on the occurence of misconception, it has a strong effect on the learning process in science of the students. These facts are among others the result of the study conducted on 26 SMAN throughout East Jawa.